Fintech in Europe : Promises and Threats - Baba, Chikako (IMF Working Papers; Working Paper, 2020)
Europe's high pre-existing level of financial development can partly account for the relatively smaller reach of fintech payment and lending activities compared to some other regions. But fintech activity is growing rapidly. Digital payment schemes are expanding within countries, although cross-border and pan-euro area instruments are not yet widespread, notwithstanding important enabling EU level regulation and the establishment of instant payments by the ECB. Automated lending models are developing but remain limited mainly to unsecured consumer lending. While start-ups are pursuing platform-based approaches under minimal regulation, there is a clear trend for fintech companies to acquire balance sheets and, relatedly, banking licenses as they expand. Meanwhile, competition is pushing many traditional banks to adopt fintech instruments, either in-house or by acquisition, thereby causing them to increasingly resemble balanced sheet-based fintech companies. These developments could improve the efficiency and reach of financial intermediation while also adding to profitability pressures for some banks. Although the COVID-19 pandemic could call into question the viability of platform-based lending fintechs funding models given that investors could face much higher delinquencies, it may also offer growth opportunities to those fintechs that are positioned to take advantage of the ongoing structural shift in demand toward virtual finance.